Centro de enseñanza de artes plásticas para niños y niñas en el Valle de los Chillos - Carrillo Viteri, Gabriela Elizabeth (2013)
The creation of the “Center for teaching and Disseminating plastic Arts for boys and girls in Valle de los Chillos” was born in response to the need of children (6 to 12 years old) and parents of the sector occupy their children in an activity that encourages education, which is why the center meets the primary goal of educating children in fine arts (painting and sculpture) to supplement their basic education and also to disseminate these arts by creating a showroom which will be easily accessible due to the sector in which it is located is the fifth residential and also some of the prominent schools in the Valle of the Chillos. The implementation of this center is conceived in the space of an old uninhabited house so with this project is to give a new use for the abandoned site, all space be organized based on the chosen concept was “Rayuela” by this element will first take the form of the element that is square, but well shafts this way, besides being a kids game that is drawn by the children themselves rescues the taste for drawing and colors so it is identified very well with the space to be created.